2017
DOI: 10.1101/102756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical activation of epithelial Na+channel relies on an interdependent activity of the extracellular matrix and extracellularN-glycans of αENaC

Abstract: Mechanotransduction describes how cells perceive their mechanical environment and mechanosensitive ion channels are important for this process. ENaC (epithelial Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…While the findings of Knoepp at al. suggested a link between ␣-subunit N-linked glycans and the channel's LSS response (35), our results seemingly rule out a role for N-linked glycans on a specific subunit in ENaC mechanosensing. Experimental differences may underlie these contrasting results.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…While the findings of Knoepp at al. suggested a link between ␣-subunit N-linked glycans and the channel's LSS response (35), our results seemingly rule out a role for N-linked glycans on a specific subunit in ENaC mechanosensing. Experimental differences may underlie these contrasting results.…”
Section: Discussionsupporting
confidence: 50%
“…These data contrast with a recent report from Knoepp at al. that implicated links between N-linked glycans on the ␣-subunit and the extracellular matrix in the channel's LSS response (35) and suggest an alternate model for how LSS regulates ENaC function (see DISCUSSION). Fig.…”
Section: Enac Activity Is Dependent On N-glycosylation Of Each Subunitmentioning
confidence: 99%
“…Endothelial ENaC activation has been proposed to blunt nitric oxide release and prevent vasodilation (24). This response appears to be flow dependent, suggesting that endothelial ENaC may be functioning as a mechanosensor (110; 111). Vascular smooth muscle ENaC has also been suggested to have a role in the pressure-induced myogenic response (25).…”
Section: Extracellular Regulators Of Enacmentioning
confidence: 99%
“…At present, it is unclear whether tethering ENaC subunits to the extracellular matrix and/or intracellular cytoskeleton is required for mechanosensing. One group has suggested that the extracellular matrix has a role in shear stress activation of ENaC in Xenopus oocytes and endothelium, and that specific α subunit N-glycans facilitate interactions between extracellular matrix and ENaC that are required for flow sensing (111). In contrast, our unpublished work (Kashlan et al) indicates that ENaC N-glycans are not required for flow sensing.…”
Section: Extracellular Regulators Of Enacmentioning
confidence: 99%
“…Sound induced vibrations lead to motion between adjacent cilia and activation of the tethered channels. The family of DEG/ENaC/ASIC channels are MSCs present in both non-specialized and specialized mechanosensory cells [24, 25], and are gated by movement of their extracellular domains [26] that are associated with the ECM [27]. This connection to the ECM is disrupted during patch formation which is likely why these channels do not show mechanosensitivity in patches [25, 28].…”
Section: Msc Gating Mechanisms and Molecular Identitymentioning
confidence: 99%